The “WiFi4EU” in light of the European Competition regime - Brandão, Diogo Nuno Cardoso Miranda de Matos (UNIO – EU Law Journal, 2018)
The “WiFi4EU” initiative is a proposal for regulation of the European Parliament and of the Council, which amends Regulations (EU) No 1316/2013 and (EU) No 283/2014, each of them on the promotion of Internet connectivity in local communities. This initiative aims to ensure that all Member States of the European Union create high-quality wireless internet access points throughout their territory to combat digital illiteracy and ensure access to healthcare, administrative services, and online commerce. With the following resolution, hospitals, libraries, monuments, museums, and parks will have a public signal available. Therefore, the proposal has a very strong social dimension, since it aims to broaden the internet signal to citizens who live near municipal areas and whose economic statuses are lacking. With a three-year implementation period, the initiative falls within the scope of the Single Digital Market, which is a major political objective and a way for the European Union to attract investments from large economic agents through the “Internet of Things”. It is therefore relevant to give some context and analyze the initiative through the eyes of the Union’s principles and of the notions of competition and regulation, which are essential to the European Union.